2014
DOI: 10.1039/c4an00066h
|View full text |Cite
|
Sign up to set email alerts
|

Dual-mode chemical vapor generation for simultaneous determination of hydride-forming and non-hydride-forming elements by atomic fluorescence spectrometry

Abstract: A dual-mode chemical vapor generation integrating hydride generation and photochemical vapor generation was developed for simultaneous multi-element analysis of hydride-forming and non-hydride-forming elements by atomic fluorescence spectrometry. Four elements were selected as model elements of hydride-forming (As, Cd) and non-hydride-forming (Ni, Fe) elements to validate this proposed method. Standard or sample solutions were separately pumped to mix with tetrahydroborate, and concentrated formic acid and amm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Also, extra heating can be obtained Relatively high PVG efficiency of Ni could be achieved in the pH range of 2.5-3.0, and Co in the relatively broader range of 1.7-2.6. This is well agreed with that reported in the literatures [16,26].…”
Section: Optimization Of Pvg Conditionssupporting
confidence: 94%
See 2 more Smart Citations
“…Also, extra heating can be obtained Relatively high PVG efficiency of Ni could be achieved in the pH range of 2.5-3.0, and Co in the relatively broader range of 1.7-2.6. This is well agreed with that reported in the literatures [16,26].…”
Section: Optimization Of Pvg Conditionssupporting
confidence: 94%
“…It has been reported that both Co and Ni achieved the best PVG efficiency in appropriate concentration of formic acid or buffer of formic acid and sodium formate with UV irradiation for 150-180 s [8,[14][15][16]26]. Here, we optimized the experimental conditions for simultaneous PVG of A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 9 Co and Ni.…”
Section: Optimization Of Pvg Conditionsmentioning
confidence: 88%
See 1 more Smart Citation
“…The UVG-AFS instrumental methods have been applied to many elemental analyses, including conventional hydrideforming elements such as Hg, [17][18][19] Se, [20][21][22] Sn, 23 As, Bi, Sb, Te, 24 Pb, 25 as well as several non-hydride-forming elements, including Fe, Co, Ni, I, and Br. 15,[26][27][28][29][30][31][32] Among them, Gao et al 25 firstly employed inorganic elements (Ni 2+ and Co 2+ ) to enhance the sensitivity of UVG of Pb. For arsenic, Zheng et al employed an UVG reaction of As(III) in acetic acid to obtain the limit of detection (LOD) of 0.5 ng mL −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the miniaturization of analytical instrumentation is making remarkable progress with the development of microelectro-mechanical systems (MEMS), micrototal analysis systems (μ-TAS), and lab-on-a-chip (LOC) technologies. Over the past two decades, various microplasmas have been developed as promising excitation sources to construct miniaturized OES, including the miniaturized MIP, low-power ICP, capacitively coupled plasma, point discharge, and dielectric barrier discharge (DBD). Due to the low excitation capacity of microplasma, analytes need to be converted to volatile species and separated from the bulk liquid phase as “dry” species prior to their excitation in the microplasma. ,, Although chemical vapor generation (CVG) can realize effective separation of analyte from liquid phase, it typically remains limited to the determination of several hydride-forming elements . Moreover, CVG techniques (particularly hydride generation, HG) produce a large amount of hydrogen, which significantly disturbs or even extinguishes microplasmas .…”
mentioning
confidence: 99%